Assessment Criteria of a Sustainable Tax System: A Literature Review - Maciej CIEŚLUKOWSKI Izabela GABRYELEWICZ; Katarzyna ŁASIŃSKA; Patryk KRUPA; Rafał KIESZEK; Grzegorz SŁOWIK (Communications of International Proceedings, 2024)
After the crisis 2008+ the criticism of traditional economics intensified and economists started to formulate alternative paths of economic development. One of them is a sustainable development based on firm and integrated economic, socio-cultural and ecological order. Such development should be supported by the rational, i.e. sustainable tax system. The clear economic slowdown due to the COVID 19 pandemic and the current climate challenges convince us that we need such a tax system. Construction of the system should begin with organization of main tax categories. The paper defines a conception of a sustainable tax system, presents main tax categories in a new economic order and shows the current fiscal importance of environmental taxes in the European Union economy.
Keywords: sustainable development; tax system; tax categories; tax system criteria assessment